The effect of application of Chlorella vulgaris extract gel on bone remodeling - Sutiyo; Astrini Desintha Iraniza; Edy Machmud (Makassar Dental Journal PDGI Makassar, 2020)
Background: Chlorella vulgaris is one type of one-celled green algae, can multiply quickly, easy to cultured, and has a high survival ability. Mineral content of C.vulgaris plays a major role in bone and teeth mineralization and the regulation of blood calcium and phosphorus levels. One way to increase the effectiveness of the use of C.vulgaris in the process of bone remo-deling is to make a formulation of C.vulgaris extract in the gel form. Objective: To determine the formulation and safety of C.vulgaris gel preparations as bone remodeling material. Method: Experimental laboratory. Conclusion: the 5% concen-tration of gel preparation of C.vulgaris is the best formulation compared to other concentrations